ESANSİYEL BLEFAROSPAZMA BAĞLI FONKSİYONEL KÖRLÜĞÜN KİMYASAL DENERVASYONLA TEDAVİSİ - BAŞAR, Emel; PAZARLI, Halit; KAYIRAN, Alp (Cerrahpaşa Medical Journal, 2019)
Background.- To evaluate the treatment of functional blindness due to prolonged eyebrow and eyelid spasm and involuntary eyelid closure in essential blepharospasm with Botulinum toxin-A. Design.- 7 patients (5 female, 2 male, average age over 35 years) with functional blindness due to essential blepharospasm were treated with Botulinum toxin (BT-A) as an outpatient procedure in the oculoplastic unit of Department of Ophthalmology, Cerrahpaşa Medical Faculty, Istanbul University. BT-A was injected subcutaneously up to different sites in the eyebrow region, medial and lateral aspects of the upper lids and lateral aspect of the lower lid as a total of 15-25 units for each eye. Mean follow-up time was 6,8 months. Results.- BT-A treatment resulted in functional improvement to open the eyelids enough to maintain daily life without visual restrictions. Mean duration of the effect was 14.5 weeks. No systemic side effects were observed. Lid ecchymosis in 3 patients and symptomatic dry eye in one patient were noted during the follow-up period. Conclusion.- BT-A treatment can improve the functional blindness in patients with essential blepharospasm temporarily by decreasing debiliating and squeezing spasms of the eyelids and eyebrows.